Topical ocular drug delivery systems: Innovations for an unmet need. (May 2022) - Yang, Yingjia; Lockwood, Alastair
Abstract: The eye is an isolated and complex organ, with multiple robust anatomical and physiological barriers on the ocular surface which protect it from noxious insults such as the blink reflex, tear film and corneoscleral tissue layers. However, these also make it difficult for drugs to reach their therapeutic target within the eye, resulting in very low bioavailability in most commercially available ophthalmic drugs. This review will detail the mechanisms present on the ocular surface which impede drug delivery and give an overview of traditional eye drop formulations, as well as methods of improving their bioavailability through viscosity and permeation enhancement. We also review the evidence for more novel technologies, such as nanoparticles, in-situ gels, blood products, and alternatives to eye drops such as drug loaded contact lenses and ocular inserts. Highlights: The anterior ocular surface has multiple anatomical and physiological barriers to drug absorption. Most commercially available eye drops achieve a bioavailability of less than 5%. Viscosity and permeation enhancers have improved the bioavailability of traditional formulations. Newer technologies have potential to enhance bioavailability and reduce side effects for better tolerated treatments.